Catalyst for preparing 1, 6-hexanediol by hydrogenation of dimethyl adipate as well as preparation method and application of catalyst
By constructing the catalyst with the interface structure between Cu and MgAl2O4, the problem of insufficient activity and stability of Cu-based catalysts in the hydrogenation reaction of dimethyl adipic acid is solved, and high activity, high selectivity and long-term stability are achieved, reducing the Production costs and equipment investment.
Patent Information
- Application Number
- CN202411233338.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-04
AI Technical Summary
The existing Cu-based catalysts are insufficient in the activity, selectivity and stability of dimethyl adipic acid hydrogenation system, and the reaction conditions are harsh, which increases production costs and equipment investment.
Using a catalyst composed of Cu and MgAl2O4 interface, Cu salt is protected by polyhydroxy ligand, precipitation using T-type mixer and hydrothermal conditions, high-temperature calcination and reduction activation, to construct highly dispersed Cu nanoparticles and MgAl2O4 phases, and spinelite Interface, improve the activity and stability of the catalyst.
The activity and selectivity of the catalyst are significantly improved under mild conditions, the stability reaches 800 hours without inactivation, simplifying the preparation process, reducing the cost of raw materials, and suitable for large-scale production.
Smart Images

Figure CN119158577A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of 1,6-hexanediol preparation, and in particular to a catalyst for preparing 1,6-hexanediol by hydrogenating dimethyl adipate, and a preparation method and application thereof. Background Art
[0002] 1,6-Hexanediol is an important diol with unique properties. It occupies an important position in the current fine chemical raw material market. It can be mixed with a variety of organic chemicals in any proportion, is non-corrosive, and can be derived into a series of new fine chemicals. It has more and more extensive applications in the fields of plasticizers, adhesives, polyurethanes, polyesters, coil coatings, and light curing. In the field of materials, 1,6-hexanediol can improve the water resistance and alkali resistance of materials, and can improve the elasticity, mechanical strength and other properties of materials. It has a wide range of applications in the fields of biodegradable polyester, high-grade synthetic fibers, and high-grade mechanical products such as automotive components. Therefore, 1,6-hexanediol is a chemical product with huge market potential.
[0003] The current synthesis methods of 1,6-hexanediol mainly include: catalytic hydrogenation of hexyne diol, epoxybutadiene method, hydroformylation method, catalytic conversion of 1,2,6-hexanetriol, catalytic conversion of 5-hydroxymethylfurfural, catalytic hydrogenation of adipic acid, sorbitol cracking method and catalytic hydrogenation of dimethyl adipate. Among them, the catalytic hydrogenation of hexyne diol has a long process route and high production cost; the conversion rate and selectivity of the epoxybutadiene method are too low to meet the production requirements; the hydroformylation method has high technical difficulty; the catalytic conversion of 1,2,6-hexanetriol, catalytic conversion of 5-hydroxymethylfurfural and sorbitol cracking methods have low product yields and high costs; the catalytic hydrogenation of adipic acid has high catalyst costs. Compared with other preparation methods, the catalytic hydrogenation of dimethyl adipate has many advantages such as fewer side reactions, high product selectivity, high product yield, easy to achieve continuous production and no corrosion to equipment. It is currently a research hotspot for the preparation of 1,6-hexanediol.
[0004] Patent CN102388009A discloses a dimethyl adipate hydrogenation catalyst, the catalyst composition is CuO: ZnO: Al2O3 = 70: 25: 5 (weight ratio), the reaction pressure is as high as 22MPa, and the catalyst activity needs to be improved. Patent CN101679157A discloses the use of a copper-zinc composite catalyst to hydrogenate alcohol in an intermittent reactor, and the reaction conditions are 275°C and 25MPa. The reaction conditions in this method are harsh, which will increase the investment in fixed equipment assets and operating costs. Patent CN110227470A discloses a CuZnAl catalyst prepared by a precipitation method, which exhibits excellent catalytic hydrogenation activity, but the catalyst stability is not disclosed.
[0005] Current research shows that Cu-based catalysts are commonly used catalysts for dimethyl adipate hydrogenation. However, the activity, selectivity and stability of Cu-based catalysts in the dimethyl adipate hydrogenation system need to be further improved. Therefore, how to design a catalytic system that can catalyze the hydrogenation of dimethyl adipate to produce 1,6-hexanediol with high activity, high selectivity and high stability under relatively mild conditions is still an urgent problem to be solved. Summary of the invention
[0006] The purpose of the present invention is to provide a catalyst for preparing 1,6-hexanediol by hydrogenating dimethyl adipate, a preparation method and application thereof, which improves the catalytic hydrogenation activity, selectivity and stability, so as to solve the shortcomings of the prior art.
[0007] The present invention adopts the following technical solutions:
[0008] A catalyst for preparing 1,6-hexanediol by hydrogenating dimethyl adipate, the catalyst comprising an active component, an auxiliary component and a carrier, wherein the active component is Cu, the auxiliary component is Mg, the high-activity reaction site is an interface formed by Cu and MgAl2O4, and the carrier is alumina; the active component is 15-45% by weight of Cu; the auxiliary component is 10%-50% by weight of Mg; and the rest is the carrier;
[0009] The catalyst is prepared by the following steps:
[0010] (I) dissolving a certain amount of soluble salt of Cu, soluble salt of Mg, soluble salt of Al and polyhydroxy ligand in a certain amount of water, which is referred to as solution 1;
[0011] (II) dissolving a certain amount of Na2CO3 and NaOH in a certain amount of water, wherein the molar ratio of Na2CO3 to NaOH is 1:2-3, which is referred to as solution 2;
[0012] (III) heating solution 1 and solution 2 to 50-80°C respectively, and injecting solution 1 and solution 2 into a T-type mixer at the same flow rate of 0.5-3 ml / min using a horizontal flow pump under heat preservation conditions, the pH after mixing is 8-10, and the resulting mixture is vigorously stirred at 400-500 rpm at 50-80°C for 3-5 hours; transferring to a sealed pressure-resistant hydrothermal autoclave, heating to 100-180°C for 8-24 hours; filtering and washing the solid until the washed liquid is neutral, and drying the washed solid in an oven at 100-180°C for 10-14 hours;
[0013] (IV) crushing the solid obtained in step (III) into small particles of less than 150 mesh and calcining them in a muffle furnace at 600-850° C. for 4-10 hours at a heating rate of 20-50° C. / min;
[0014] (V) The solid obtained in step (IV) is reduced and activated in a reduction activation furnace at 300-450° C. for 10-12 h, the reduction activation heating rate is 20-50° C. / min, the reduction activation gas is H2 or H2 / inert gas mixture, and the reduction activation gas space velocity is 1000-3000 h -1 , the reduction activation pressure is normal pressure; after reduction activation, the temperature is lowered to room temperature, and a small amount of air is introduced into a nitrogen atmosphere for passivation treatment. The passivation treatment operation is repeated 2-4 times, with an interval of 5-10 minutes between each passivation treatment. During this period, nitrogen is always introduced to obtain the catalyst.
[0015] Furthermore, the active component is calculated by the mass of Cu element, and its content is 15-35%; the auxiliary component is calculated by the mass of Mg element, and its content is 15%-45%; and the rest is carrier.
[0016] Furthermore, in step (I), the soluble salt of Cu is one or more of copper chloride, copper sulfate, copper nitrate, and copper acetate, the soluble salt of Mg is one or both of magnesium nitrate and magnesium chloride, the soluble salt of Al is one or both of aluminum nitrate and aluminum chloride, and the polyhydroxy ligand is glucose, citric acid, and salicylic acid. Furthermore, in step (I), the molar ratio of the polyhydroxy ligand to the two metal ions of Cu and Mg in solution 1 is 0.1-1:1, and the total molar concentration of the soluble salts of Cu, soluble salts of Mg, and soluble salts of Al is 1.5-2.5 mol / L; in step (II), the total molar concentration of Na2CO3 and NaOH in solution 2 is 4.5-5.5 mol / L; in step (III), the ratio of the total amount of the soluble salts of Cu, soluble salts of Mg, and soluble salts of Al in solution 1 to the total amount of Na2CO3 and NaOH in solution 2 is 1:2.2-3.
[0017] A method for preparing a catalyst for preparing 1,6-hexanediol by hydrogenating dimethyl adipate comprises the following steps:
[0018] (I) dissolving a certain amount of soluble salt of Cu, soluble salt of Mg, soluble salt of Al and polyhydroxy ligand in a certain amount of water, which is referred to as solution 1;
[0019] (II) dissolving a certain amount of Na2CO3 and NaOH in a certain amount of water, wherein the molar ratio of Na2CO3 to NaOH is 1:2-3, which is referred to as solution 2;
[0020] (III) heating solution 1 and solution 2 to 50-80°C respectively, and injecting solution 1 and solution 2 into a T-type mixer at the same flow rate of 0.5-3 ml / min using a horizontal flow pump under heat preservation conditions, the pH after mixing is 8-10, and the resulting mixture is vigorously stirred at 400-500 rpm at 50-80°C for 3-5 hours; transferring to a sealed pressure-resistant hydrothermal autoclave, heating to 100-180°C for 8-24 hours; filtering and washing the solid until the washed liquid is neutral, and drying the washed solid in an oven at 100-180°C for 10-14 hours;
[0021] (IV) crushing the solid obtained in step (III) into small particles of less than 150 mesh and calcining them in a muffle furnace at 600-850° C. for 4-10 hours at a heating rate of 20-50° C. / min;
[0022] (V) The solid obtained in step (IV) is reduced and activated in a reduction activation furnace at 300-450° C. for 10-12 h, the reduction activation heating rate is 20-50° C. / min, the reduction activation gas is H2 or H2 / inert gas mixture, and the reduction activation gas space velocity is 1000-3000 h -1 , the reduction activation pressure is normal pressure; after reduction activation, the temperature is lowered to room temperature, a small amount of air is introduced into a nitrogen atmosphere for passivation treatment, the passivation treatment operation is repeated 2-4 times, each passivation treatment interval is 5-10min, and nitrogen is always introduced during the period to obtain the catalyst;
[0023] The catalyst comprises an active component, an auxiliary component and a carrier, wherein the active component is Cu, the auxiliary component is Mg, the high-activity reaction site is the interface formed by Cu and MgAl2O4, and the carrier is alumina; the active component is 15-45% by weight of Cu; the auxiliary component is 10%-50% by weight of Mg; and the rest is the carrier.
[0024] Furthermore, the active component is calculated based on the mass of Cu element, and its content is 15-35%; the auxiliary component is calculated based on the mass of Mg element, and its content is 15%-45%; and the rest is carrier.
[0025] Furthermore, in step (I), the soluble salt of Cu is one or more of copper chloride, copper sulfate, copper nitrate, and copper acetate, the soluble salt of Mg is one or both of magnesium nitrate and magnesium chloride, the soluble salt of Al is one or both of aluminum nitrate and aluminum chloride, and the polyhydroxy ligand is one or more of glucose, citric acid, salicylic acid, and phytic acid.
[0026] Furthermore, in step (I), the molar ratio of the polyhydroxy ligand to the two metal ions of Cu and Mg in solution 1 is 0.1-1:1, and the total molar concentration of the soluble salts of Cu, soluble salts of Mg and soluble salts of Al is 1.5-2.5 mol / L; in step (II), the total molar concentration of Na2CO3 and NaOH in solution 2 is 4.5-5.5 mol / L; in step (III), the ratio of the total amount of the soluble salts of Cu, soluble salts of Mg and soluble salts of Al in solution 1 to the total amount of Na2CO3 and NaOH in solution 2 is 1:2.2-3.
[0027] Application of the catalyst in the selective hydrogenation of dimethyl adipate to prepare 1,6-hexanediol.
[0028] Furthermore, the application includes the following steps: firstly, the catalyst is loaded into a packed bed reactor, and the entire reaction tube is filled with quartz sand; the catalyst is reduced in H2 or H2 / inert gas mixture before use, and the reduction conditions are: the H2 or H2 / inert gas mixture gas space velocity is 50-3000h -1 , the reduction pressure is 0.1-1.0MPa, the reduction temperature is 250-350℃, the reduction heating rate is 0.1-10℃ / min, and the reduction time is 0.5-18h; after the reduction is completed, the gas is switched to H2, and the reaction conditions are adjusted to the specified reaction conditions, and dimethyl adipate or a mixture of 10-40wt% dimethyl adipate and methanol is pumped in. The reaction conditions are: the liquid hourly space velocity of dimethyl adipate is 0.05-3.0h -1 , the molar ratio of H2: dimethyl adipate is 5-300:1, the reaction temperature is 60-350°C, and the reaction pressure is 1.0-7.0MPa.
[0029] Beneficial effects of the present invention:
[0030] 1. The high-performance diester hydrogenation catalyst prepared by the present invention activates H2 with highly dispersed Cu nanoparticles, enhances the adsorption and activation of ester groups by means of the interface composed of Cu and MgAl2O4, and inhibits the sintering and growth of Cu nanoparticles during the reaction by means of the super stability of MgAl2O4, thereby improving the stability of the catalyst. In the catalyst preparation process, firstly, the Cu salt in the solution is protected by polyhydroxy ligands to prevent the Cu salt from forming large particles during the precipitation process; then, the metal salt solution and the alkali solution are mixed by a T-type mixer, which can more fully mix the solution, making the reaction more uniform and rapid, and avoiding loss or waste; further, the hydrotalcite precursor doped with polyhydroxy organic ligands is generated by dissolving and reconstructing the precipitate under hydrothermal conditions; then, a phase with highly dispersed Cu nanoparticles and MgAl2O4 is synthesized in the process of rapid high-temperature roasting and in vitro reduction activation to construct a high-performance catalyst precursor; finally, by means of in-situ reduction, an interface composed of Cu and MgAl2O4 is constructed at a local position to further improve the hydrogenation activity and stability of the catalyst, and a highly dispersed copper interface wrapped in spinel is constructed by two-step reduction. The highly dispersed Cu and the interface composed of Cu and MgAl2O4 not only promote the adsorption and activation of dimethyl adipate and H2, but also significantly improve the catalyst stability.
[0031] 2. The high-performance Cu-based catalyst of the present invention can have high activity and high selectivity under mild reaction conditions during the hydrogenation reaction of dimethyl adipate. The construction of the microscopic spinel interface on the catalyst surface has extremely high stability, and the catalyst is stable for 800 hours without deactivation. The catalyst preparation method of the present invention is simple, has good repeatability, and has low raw material prices. The catalyst has high activity, good selectivity, good stability, and is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of a T-type mixer; a and b are branch pipes for introducing fluid, and the liquid is transported through the input pipe, and c represents the output pipe, which flows out of the mixer.
[0033] Figure 2 These are the SEM and elemental analysis images of the catalyst of Example 1.
[0034] Figure 3 This is a TEM image of the catalyst of Example 1.
[0035] Figure 4 is the XRD pattern of the catalyst of Example 1.
[0036] Figure 5 This is a performance stability test chart of the catalyst of Example 1 when the product is 1,6-hexanediol. DETAILED DESCRIPTION
[0037] The present invention is further explained below in conjunction with the examples and drawings. The following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0038] Example 1
[0039] Dissolve 7.6 g copper nitrate trihydrate, 22.4 g magnesium nitrate hexahydrate, 33.1 g aluminum nitrate nonahydrate and 4.0 g glucose in 100 mL deionized water, which is called solution 1. Dissolve 12.6 g Na2CO3 and 14.3 g NaOH in 100 mL deionized water, which is called solution 2. Heat solution 1 and solution 2 to 65°C, respectively, and inject solution 1 and solution 2 into a T-type mixer (such as a 100 mL mixer) at a flow rate of 2 mL / min using a horizontal flow pump under the same temperature. Figure 1 As shown, the same below), the pH after mixing is 9.5, the resulting mixture is vigorously stirred at 500 rpm in a 65°C beaker for 3 hours; transferred to a sealed pressure-resistant hydrothermal kettle (Shanghai Yanzheng Experimental Instrument Co., Ltd. hydrothermal reactor (YZHR-200-E)), heated to 100°C for 10 hours; filtered and washed the solid until the washed liquid is neutral, put the washed solid in an oven at 120°C for 12 hours, crushed the solid into small particles below 150 mesh, and calcined at 620°C in a muffle furnace for 5 hours, with a calcination heating rate of 20°C / min; the solid was reduced and activated at 300°C in a reduction activation furnace for 10 hours, with a reduction activation heating rate of 20°C / min, the reduction activation gas is H2, and the H2 gas space velocity is 1500h -1 , the reduction activation pressure is normal pressure; after reduction activation, the temperature is lowered to room temperature, and a small amount of air (about 40 ml) is introduced in a nitrogen atmosphere for passivation treatment. The passivation treatment operation is repeated three times, with an interval of 10 minutes between each passivation treatment, and nitrogen is always introduced during the period to obtain a catalyst. The obtained catalyst is named 1-Cu / MgAlO.
[0040] The catalyst 1-Cu / MgAlO prepared in this embodiment, such as Figure 2-4 As shown, Figure 2 This shows that the active components Cu, Mg, and Al in the catalyst are evenly distributed on the catalyst surface and are tightly bound; Figure 3 It shows that the Cu nanoparticles on the catalyst surface are uniformly distributed and small in size; Figure 4 It shows that the catalyst surface has highly dispersed Cu and MgAl2O4 species.
[0041] Take 1.0 g of the above-mentioned small particle catalyst 1-Cu / MgAlO crushed to less than 150 mesh and load it into a packed bed reactor. Fill the entire reaction tube with quartz sand to reduce the catalyst. The reducing gas is a H2 / N2 mixed gas with a H2 content of 10% v / v. The gas space velocity of the mixed gas is 1500 h -1, the reduction pressure is 0.3MPa, the reduction temperature is 300℃, the reduction heating rate is 1℃ / min, and the reduction time is 4h; after the reduction is completed, the gas is switched to H2, adjusted to the specified reaction conditions, and dimethyl adipate is pumped in using a high-pressure plunger pump. The reaction conditions are: the liquid hourly space velocity of dimethyl adipate is 0.2h -1 , the molar ratio of H2: dimethyl adipate was 60:1, the reaction temperature was 220°C, and the reaction pressure was 3.0 MPa. The conversion rate of dimethyl adipate was 100%, and the selectivity of 1,6-hexanediol was 98.8%.
[0042] Example 2
[0043] 11.4 g of copper nitrate trihydrate, 22.4 g of magnesium nitrate hexahydrate, 25.6 g of aluminum nitrate nonahydrate and 4.0 g of glucose were dissolved in 100 mL of deionized water, which was recorded as solution 1. 11.9 g of Na2CO3 and 13.4 g of NaOH were dissolved in 100 mL of deionized water, which was recorded as solution 2. Solution 1 and solution 2 were heated to 65°C respectively. Under heat preservation conditions, solution 1 and solution 2 were injected into a T-type mixer at a flow rate of 2 mL / min using a horizontal flow pump. The pH after mixing was 9.5. The resulting mixture was vigorously stirred at 500 rpm in a 65°C beaker for 3 h; transferred to a sealed pressure-resistant hydrothermal reactor (Shanghai Yanzheng Experimental Instrument Co., Ltd. hydrothermal reactor (YZHR-200-E)), heated to 100°C for 10 h; filtered and washed the solid until the washed liquid was neutral, placed the washed solid in an oven at 120°C for 12 h, crushed the obtained solid into small particles below 150 mesh, and calcined at 620°C in a muffle furnace for 5 h, with a calcination heating rate of 20°C / min; the obtained solid was reduced and activated at 300°C in a reduction activation furnace for 10 h, with a reduction activation heating rate of 20°C / min, and the reduction activation gas was H2, with a H2 gas space velocity of 1500 h -1 , the reduction activation pressure is normal pressure; after reduction activation, the temperature is lowered to room temperature, and a small amount of air (about 40 ml) is introduced in a nitrogen atmosphere for passivation treatment. The passivation treatment operation is repeated three times, with an interval of 10 minutes between each passivation treatment, and nitrogen is always introduced during the period to obtain a catalyst. The obtained catalyst is named 2-Cu / MgAlO.
[0044] 1.0 g of the above-mentioned small particle catalyst 2-Cu / MgAlO crushed to less than 150 mesh was loaded into a packed bed reactor, and the entire reaction tube was filled with quartz sand to reduce the catalyst. The reducing gas was a H2 / N2 mixed gas with a H2 content of 10% v / v, and the gas space velocity of the mixed gas was 1500 h -1, the reduction pressure is 0.3MPa, the reduction temperature is 300℃, the reduction heating rate is 1℃ / min, and the reduction time is 4h; after the reduction is completed, the gas is switched to H2, adjusted to the specified reaction conditions, and dimethyl adipate is pumped in using a high-pressure plunger pump. The reaction conditions are: the liquid hourly space velocity of dimethyl adipate is 0.2h -1 , the molar ratio of H2: dimethyl adipate was 60:1, the reaction temperature was 220°C, and the reaction pressure was 3.0 MPa. The conversion rate of dimethyl adipate was 100%, and the selectivity of 1,6-hexanediol was 98.0%.
[0045] Example 3
[0046] 7.6 g of copper nitrate trihydrate, 22.4 g of magnesium nitrate hexahydrate, 33.1 g of aluminum nitrate nonahydrate and 4.0 g of citric acid were dissolved in 100 mL of deionized water, which was recorded as solution 1. 12.6 g of Na2CO3 and 14.3 g of NaOH were dissolved in 100 mL of deionized water, which was recorded as solution 2. Solution 1 and solution 2 were heated to 65°C respectively. Under heat preservation conditions, solution 1 and solution 2 were injected into a T-type mixer at a flow rate of 2 mL / min using a horizontal flow pump. The pH after mixing was 9.5. The resulting mixture was vigorously stirred at 500 rpm in a 65°C beaker for 3 h; transferred to a sealed pressure-resistant hydrothermal reactor (Shanghai Yanzheng Experimental Instrument Co., Ltd. hydrothermal reactor (YZHR-200-E)), heated to 100°C for 10 h; filtered and washed the solid until the washed liquid was neutral, placed the washed solid in an oven at 120°C for 12 h, crushed the obtained solid into small particles below 150 mesh, and calcined at 620°C in a muffle furnace for 5 h, with a calcination heating rate of 20°C / min; the obtained solid was reduced and activated at 300°C in a reduction activation furnace for 10 h, with a reduction activation heating rate of 20°C / min, and the reduction activation gas was H2, with a H2 gas space velocity of 1500 h -1 , the reduction activation pressure is normal pressure; after reduction activation, the temperature is lowered to room temperature, and a small amount of air (about 40 ml) is introduced in a nitrogen atmosphere for passivation treatment. The passivation treatment operation is repeated three times, with an interval of 10 minutes between each passivation treatment, and nitrogen is always introduced during the period to obtain a catalyst. The obtained catalyst is named 3-Cu / MgAlO.
[0047] 1.0 g of the above-mentioned small-particle catalyst 3-Cu / MgAlO crushed to less than 150 mesh was loaded into a packed bed reactor, and the entire reaction tube was filled with quartz sand to reduce the catalyst. The reducing gas was a H2 / N2 mixed gas with a H2 content of 10% v / v, and the gas space velocity of the mixed gas was 1500 h -1, the reduction pressure is 0.3MPa, the reduction temperature is 300℃, the reduction heating rate is 1℃ / min, and the reduction time is 4h; after the reduction is completed, the gas is switched to H2, adjusted to the specified reaction conditions, and dimethyl adipate is pumped in using a high-pressure plunger pump. The reaction conditions are: the liquid hourly space velocity of dimethyl adipate is 0.2h -1 , the molar ratio of H2: dimethyl adipate was 60:1, the reaction temperature was 220°C, and the reaction pressure was 3.0 MPa. The conversion rate of dimethyl adipate was 100%, and the selectivity of 1,6-hexanediol was 98.5%.
[0048] Example 4
[0049] 7.6 g of copper nitrate trihydrate, 22.4 g of magnesium nitrate hexahydrate, 33.1 g of aluminum nitrate nonahydrate and 4.0 g of salicylic acid were dissolved in 100 mL of deionized water, which was recorded as solution 1. 12.6 g of Na2CO3 and 14.3 g of NaOH were dissolved in 100 mL of deionized water, which was recorded as solution 2. Solution 1 and solution 2 were heated to 65°C respectively. Under heat preservation conditions, solution 1 and solution 2 were injected into a T-type mixer at a flow rate of 2 mL / min using a horizontal flow pump. The pH after mixing was 9.5. The resulting mixture was vigorously stirred at 500 rpm in a 65°C beaker for 3 h; transferred to a sealed pressure-resistant hydrothermal reactor (Shanghai Yanzheng Experimental Instrument Co., Ltd. hydrothermal reactor (YZHR-200-E)), heated to 100°C for 10 h; filtered and washed the solid until the washed liquid was neutral, placed the washed solid in an oven at 120°C for 12 h, crushed the obtained solid into small particles below 150 mesh, and calcined at 620°C in a muffle furnace for 5 h, with a calcination heating rate of 20°C / min; the obtained solid was reduced and activated at 300°C in a reduction activation furnace for 10 h, with a reduction activation heating rate of 20°C / min, and the reduction activation gas was H2, with a H2 gas space velocity of 1500 h -1 , the reduction activation pressure is normal pressure; after reduction activation, the temperature is lowered to room temperature, and a small amount of air (about 40 ml) is introduced in a nitrogen atmosphere for passivation treatment. The passivation treatment operation is repeated three times, with an interval of 10 minutes between each passivation treatment, and nitrogen is always introduced during the period to obtain a catalyst. The obtained catalyst is named 4-Cu / MgAlO.
[0050] 1.0 g of the above-mentioned small particle catalyst 4-Cu / MgAlO crushed to less than 150 mesh was loaded into a packed bed reactor, and the entire reaction tube was filled with quartz sand to reduce the catalyst. The reducing gas was a H2 / N2 mixed gas with a H2 content of 10% v / v, and the gas space velocity of the mixed gas was 1500 h -1, the reduction pressure is 0.3MPa, the reduction temperature is 300℃, the reduction heating rate is 1℃ / min, and the reduction time is 4h; after the reduction is completed, the gas is switched to H2, adjusted to the specified reaction conditions, and dimethyl adipate is pumped in using a high-pressure plunger pump. The reaction conditions are: the liquid hourly space velocity of dimethyl adipate is 0.2h -1 , the molar ratio of H2: dimethyl adipate was 60:1, the reaction temperature was 220°C, and the reaction pressure was 3.0 MPa. The conversion rate of dimethyl adipate was 100%, and the selectivity of 1,6-hexanediol was 98.2%.
[0051] Example 5
[0052] The catalyst 1-Cu / MgAlO in Example 1 was used to conduct a stability test experiment for preparing 1,6-hexanediol by hydrogenation of dimethyl adipate. The experiment found that under the same reduction and reaction conditions as Example 1, the catalyst performance analysis showed that the catalyst was not significantly deactivated after 800 hours of reaction. Figure 5 The blue arrow represents the conversion rate of dimethyl adipate, and the red arrow represents the selectivity of 1,6-hexanediol, which indicates that the catalyst has excellent stability when the product is 1,6-hexanediol.
[0053] Comparative Example 1
[0054] The R1-Cu / MgAlO catalyst was prepared by the conventional co-impregnation method. The MgAlO carrier was synthesized by itself. The specific steps were as follows: 28.0 g of magnesium nitrate hexahydrate, 41.4 g of aluminum nitrate nonahydrate and 4.0 g of glucose were dissolved in 100 mL of deionized water, which was recorded as solution 1. 13.4 g of Na2CO3 and 15.2 g of NaOH were dissolved in 100 mL of deionized water, which was recorded as solution 2. Solution 1 and solution 2 were heated to 65°C respectively. Under heat preservation conditions, solution 1 and solution 2 were injected into a T-type mixer at a flow rate of 2 mL / min using a horizontal flow pump. The pH after mixing was 9.5. The resulting mixture was vigorously stirred at 500 rpm in a 65°C beaker for 3 h; transferred to a sealed pressure-resistant hydrothermal reactor (Shanghai Yanzheng Experimental Instrument Co., Ltd. hydrothermal reactor (YZHR-200-E)), heated to 100°C for 10 h; filtered and washed the solid until the washed liquid was neutral, placed the washed solid in an oven at 120°C for 12 h, crushed the obtained solid into small particles below 150 mesh, and then roasted in a muffle furnace at 620°C 5h, the roasting heating rate is 20℃ / min, and a white solid MgAlO carrier is obtained; then the metal Cu is loaded, and the specific steps are as follows: 3.4g of copper nitrate trihydrate is dissolved in 3ml of deionized water, and then 3g of the prepared MgAlO carrier (below 150 mesh) is added, stirred evenly, dried under natural conditions, placed in an oven at 120℃ for 5h, and then roasted in a muffle furnace at 620℃ for 5h, and the roasting heating rate is 20℃ / min; the obtained solid is reduced and activated at 300℃ in a reduction activation furnace for 10h, the reduction activation heating rate is 20℃ / min, the reduction activation gas is H2, and the H2 gas space velocity is 1500h -1 , the reduction activation pressure is normal pressure; after reduction activation, the temperature is lowered to room temperature, and a small amount of air (about 40 ml) is injected into the nitrogen atmosphere for passivation treatment. The passivation treatment operation is repeated three times, and each passivation treatment is separated by 10 minutes. During this period, nitrogen is always introduced to obtain a catalyst. The obtained catalyst is named R1-Cu / MgAlO. The catalytic performance test is carried out under the reduction and reaction conditions of Example 1. The conversion rate of dimethyl adipate is 37%, and the selectivity of 1,6-hexanediol is 30%.
[0055] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A catalyst for preparing 1,6-hexanediol by hydrogenating dimethyl adipate, characterized in that: The catalyst comprises an active component, an auxiliary component and a carrier, wherein the active component is Cu, the auxiliary component is Mg, the high-activity reaction site is the interface formed by Cu and MgAl2O4, and the carrier is alumina; the active component is 15-45% by weight of Cu; the auxiliary component is 10%-50% by weight of Mg; and the rest is the carrier; The catalyst is prepared by the following steps: (I) dissolving a certain amount of soluble salt of Cu, soluble salt of Mg, soluble salt of Al and polyhydroxy ligand in a certain amount of water, which is referred to as solution 1; (II) dissolving a certain amount of Na2CO3 and NaOH in a certain amount of water, wherein the molar ratio of Na2CO3 to NaOH is 1:2-3, which is referred to as solution 2; (III) heating solution 1 and solution 2 to 50-80°C respectively, and injecting solution 1 and solution 2 into a T-type mixer at the same flow rate of 0.5-3 ml / min using a horizontal flow pump under heat preservation conditions, the pH of the mixture is 8-10 after mixing, and the resulting mixture is vigorously stirred at 400-500 rpm at 50-80°C for 3-5 hours; transferring the mixture to a sealed pressure-resistant hydrothermal autoclave, heating it to 100-180°C and treating it for 8-24 hours; Filter and wash the solid until the washed liquid is neutral, and put the washed solid into an oven at 100-180°C to dry for 10-14h; (IV) crushing the solid obtained in step (III) into small particles of less than 150 mesh and calcining them in a muffle furnace at 600-850° C. for 4-10 hours at a heating rate of 20-50° C. / min; (V) The solid obtained in step (IV) is reduced and activated in a reduction activation furnace at 300-450° C. for 10-12 h, the reduction activation heating rate is 20-50° C. / min, the reduction activation gas is H2 or H2 / inert gas mixture, and the reduction activation gas space velocity is 1000-3000 h -1 , the reduction activation pressure is normal pressure; after reduction activation, the temperature is lowered to room temperature, and a small amount of air is introduced into a nitrogen atmosphere for passivation treatment. The passivation treatment operation is repeated 2-4 times, and each passivation treatment is separated by 5-10 minutes. During this period, nitrogen is always introduced to obtain the catalyst.
2. A catalyst for preparing 1,6-hexanediol by hydrogenation of dimethyl adipate according to claim 1, characterized in that: The active component is calculated based on the mass of Cu element, and its content is 15-35%; the auxiliary component is calculated based on the mass of Mg element, and its content is 15%-45%; and the rest is carrier.
3. A catalyst for preparing 1,6-hexanediol by hydrogenation of dimethyl adipate according to claim 1, characterized in that: In step (I), the soluble salt of Cu is one or more of copper chloride, copper sulfate, copper nitrate, and copper acetate, the soluble salt of Mg is one or both of magnesium nitrate and magnesium chloride, the soluble salt of Al is one or both of aluminum nitrate and aluminum chloride, and the polyhydroxy ligand is one or more of glucose, citric acid, salicylic acid, and phytic acid.
4. A catalyst for preparing 1,6-hexanediol by hydrogenation of dimethyl adipate according to claim 1, characterized in that: In step (I), the molar ratio of the polyhydroxy ligand to the two metal ions of Cu and Mg in solution 1 is 0.1-1:1, and the total molar concentration of the soluble salts of Cu, soluble salts of Mg and soluble salts of Al is 1.5-2.5 mol / L; in step (II), the total molar concentration of Na2CO3 and NaOH in solution 2 is 4.5-5.5 mol / L; in step (III), the ratio of the total amount of the soluble salts of Cu, soluble salts of Mg and soluble salts of Al in solution 1 to the total amount of the soluble salts of Na2CO3 and NaOH in solution 2 is 1:2.2-3.
5. A method for preparing a catalyst for hydrogenating dimethyl adipate to prepare 1,6-hexanediol, characterized in that: The steps include: (I) dissolving a certain amount of soluble salt of Cu, soluble salt of Mg, soluble salt of Al and polyhydroxy ligand in a certain amount of water, which is referred to as solution 1; (II) dissolving a certain amount of Na2CO3 and NaOH in a certain amount of water, wherein the molar ratio of Na2CO3 to NaOH is 1:2-3, which is referred to as solution 2; (III) heating solution 1 and solution 2 to 50-80°C respectively, and injecting solution 1 and solution 2 into a T-type mixer at the same flow rate of 0.5-3 ml / min using a horizontal flow pump under heat preservation conditions, the pH of the mixture is 8-10 after mixing, and the resulting mixture is vigorously stirred at 400-500 rpm at 50-80°C for 3-5 hours; transferring the mixture to a sealed pressure-resistant hydrothermal autoclave, heating it to 100-180°C and treating it for 8-24 hours; Filter and wash the solid until the washed liquid is neutral, and put the washed solid into an oven at 100-180°C to dry for 10-14h; (IV) crushing the solid obtained in step (III) into small particles of less than 150 mesh and calcining them in a muffle furnace at 600-850° C. for 4-10 hours at a heating rate of 20-50° C. / min; (V) The solid obtained in step (IV) is reduced and activated in a reduction activation furnace at 300-450° C. for 10-12 h, the reduction activation heating rate is 20-50° C. / min, the reduction activation gas is H2 or H2 / inert gas mixture, and the reduction activation gas space velocity is 1000-3000 h -1 , the reduction activation pressure is normal pressure; after reduction activation, the temperature is lowered to room temperature, a small amount of air is introduced into a nitrogen atmosphere for passivation treatment, the passivation treatment operation is repeated 2-4 times, each passivation treatment interval is 5-10min, and nitrogen is always introduced during the period to obtain the catalyst; The catalyst comprises an active component, an auxiliary component and a carrier, wherein the active component is Cu, the auxiliary component is Mg, the high-activity reaction site is the interface formed by Cu and MgAl2O4, and the carrier is alumina; the active component is 15-45% by weight of Cu; the auxiliary component is 10%-50% by weight of Mg; and the rest is the carrier.
6. The method for preparing a catalyst for preparing 1,6-hexanediol by hydrogenating dimethyl adipate according to claim 5, characterized in that: The active component is calculated based on the mass of Cu element, and its content is 15-35%; the auxiliary component is calculated based on the mass of Mg element, and its content is 15%-45%; and the rest is carrier.
7. The method for preparing a catalyst for preparing 1,6-hexanediol by hydrogenating dimethyl adipate according to claim 5, characterized in that: In step (I), the soluble salt of Cu is one or more of copper chloride, copper sulfate, copper nitrate, and copper acetate, the soluble salt of Mg is one or both of magnesium nitrate and magnesium chloride, the soluble salt of Al is one or both of aluminum nitrate and aluminum chloride, and the polyhydroxy ligand is one or more of glucose, citric acid, salicylic acid, and phytic acid.
8. The method for preparing a catalyst for preparing 1,6-hexanediol by hydrogenating dimethyl adipate according to claim 5, characterized in that: In step (I), the molar ratio of the polyhydroxy ligand to the two metal ions of Cu and Mg in solution 1 is 0.1-1:1, and the total molar concentration of the soluble salts of Cu, soluble salts of Mg and soluble salts of Al is 1.5-2.5 mol / L; in step (II), the total molar concentration of Na2CO3 and NaOH in solution 2 is 4.5-5.5 mol / L; in step (III), the ratio of the total amount of the soluble salts of Cu, soluble salts of Mg and soluble salts of Al in solution 1 to the total amount of the soluble salts of Na2CO3 and NaOH in solution 2 is 1:2.2-3.
9. Use of the catalyst according to any one of claims 1 to 4 in the selective hydrogenation of dimethyl adipate to produce 1,6-hexanediol.
10. The use according to claim 9, characterized in that: The application comprises the following steps: firstly, the catalyst is loaded into a packed bed reactor, and the entire reaction tube is filled with quartz sand; the catalyst is reduced in H2 or H2 / inert gas mixture before use, and the reduction conditions are: the H2 or H2 / inert gas mixture gas space velocity is 50-3000h -1 , the reduction pressure is 0.1-1.0MPa, the reduction temperature is 250-350℃, the reduction heating rate is 0.1-10℃ / min, and the reduction time is 0.5-18h; after the reduction is completed, the gas is switched to H2, and the reaction conditions are adjusted to the specified reaction conditions, and dimethyl adipate or a mixture of 10-40wt% dimethyl adipate and methanol is pumped in. The reaction conditions are: the liquid hourly space velocity of dimethyl adipate is 0.05-3.0h -1 , the molar ratio of H2: dimethyl adipate is 5-300:1, the reaction temperature is 60-350°C, and the reaction pressure is 1.0-7.0MPa.
Citation Information
Patent Citations
Catalyst for preparing hexanediol from dimethyl adipate and preparation method and application thereof
CN105727962A
Catalyst and method for preparing 1, 6-hexanediol by hydrogenation of dialkyl 1, 6-adipate
CN106607044A
Catalyst for preparing 1, 6-hexanediol through reduction of adipic acid and preparation method
CN116493022A
Catalyst for preparing 1, 6-hexanediol through dimethyl adipate hydrogenation and preparation method and application thereof
CN118384893A
process for the preparation of a catalyst for the reduction of esters to alcohols
FR1276722A
Cited By
Continuous preparation method of dihydric alcohol
CN122647319A
